Classification of companies into stock exchange quotation markets using network metrics - Siudak, Dariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The classification of a company into the relevant quotation market is an essential part of stock market efficiency. The aim of the article is to predict the classification of enterprises into the two types of quotation markets on the Warsaw Stock Exchange (i.e. the main one and NewConnect) by means of network measures of the company’s participation in interlocking directorates’ networks. The research was carried out on a network of enterprises established on the basis of their relationships through shared board directors. This network included 460 companies listed on the main exchange, and 442 companies in the NewConnect markets of the Warsaw Stock Exchange respectively (a total of 902 entities) at the end of 2014. The aim of the study is to classify the companies into the appropriate quotation market on the Warsaw Stock Exchange, i.e. the main market (WSE) or NewConnect (NC)
Argumenta Oeconomica, 2020, Nr 2 (45), s. 275-292
Keywords: classification; social network; interlocking directorates; network metrics